2024
DOI: 10.3164/jcbn.23-96
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity exercise impairs intestinal barrier function by generating oxidative stress

Maki Takami,
Wataru Aoi,
Karin Matsumoto
et al.

Abstract: The intestine functions as a barrier preventing the entry of extrinsic factors into the body. This barrier function is disrupted by oxidative damage along with an impaired mucosal layer. Excessive exercise can generate oxidative stress in the intestinal tissue; however, the effect of exercise-induced oxidative stress on intestinal permeability is unclear. In this study, we examined the involvement of oxidative stress in barrier function of the ileum of mice following high-intensity exercise. Male ICR mice (12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Oxidative stress response has the potential to induce damage to the intestinal barrier, with MUC2 serving as a crucial marker for its integrity. SH can enhance the secretion of MUC2, thus effectively mitigating STC, which aligns with the existing literature findings [47,48]. This study reveals the upregulating effects of SH on SOD1 and MUC2, as well as its downregulating effects on AQP1, highlighting the potential regulatory roles of these targets.…”
Section: Discussionsupporting
confidence: 90%
“…Oxidative stress response has the potential to induce damage to the intestinal barrier, with MUC2 serving as a crucial marker for its integrity. SH can enhance the secretion of MUC2, thus effectively mitigating STC, which aligns with the existing literature findings [47,48]. This study reveals the upregulating effects of SH on SOD1 and MUC2, as well as its downregulating effects on AQP1, highlighting the potential regulatory roles of these targets.…”
Section: Discussionsupporting
confidence: 90%
“…Recent research revealed that excessive exercise training for 2 weeks led to higher levels of oxidative proteins and triggered high-intensity permeability and tight-junction damage. Inhibition of ROS production suppressed the elevation of intestinal permeability induced by exercise [ 74 ]. Moreover, pro-inflammatory cytokines such as IL-6, IL-1β, TNF-α, and NF-κB are also elevated during intense exercise [ 75 ].…”
Section: The Mechanisms Of the Gut Microbiota With Respect To Exercis...mentioning
confidence: 99%